LOCAL WISDOM OF EARTH ALMS TRADITION AND ITS APPLICATION IN THE COMMUNITY IN DUSUN NYURUNGAN, MENDURAN VILLAGE, GROBOGAN DISTRICT - Agustina, Erlina Farah (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
This research is based on the local wisdom of almsgiving to the earth which is always carried out by the people of Dusun Nyurungan, Menduran Village, Grobogan Regency every year. The aim of this research is to find out what almsgiving is and how it is implemented in society. The research method used is descriptive qualitative with data collection techniques in the form of interviews with community leaders, documentation and literature study. The results of the research show that in this earth alms tradition the buffalo is used as a medium. This animal is later slaughtered in one of the residents' houses and then the meat is distributed to the village community. Earth almsgiving is also carried out as a form of gratitude to Allah SWT for all his abundance. Apart from that, earth almsgiving itself has the values of mutual cooperation, faith, kinship, justice, friendship and the value of prayer.  Obstacles in implementation can occur due to internal and external factors. This shows that giving earth alms has been a tradition in Dusun Nyurungan since time immemorial and will not be replaced as time goes by.